Electronic and optical properties of graphene, silicene, germanene, and their semi-hydrogenated systems. Issue 54 (6th December 2022) - Khuong Dien, Vo; Li, Wei-Bang; Lin, Kuang-I.; Thi Han, Nguyen; Lin, Ming-Fa
Abstract : We investigate the geometric, electric, and optical properties of two-dimensional honeycomb lattices using first-principles simulations. Abstract : We investigate the geometric, electric, and optical properties of two-dimensional honeycomb lattices using first-principles simulations. The main focus of this work is on the similarities and differences in their characteristics, as well as the delicate connection of orbital hybridizations and spin-polarizations with electronic and optical properties. Graphene, silicene, germanene, and their semi-hydrogenated systems, in turn, display sp 2, sp 2 –sp 3, and sp 3 s hybridizations. These bonding configurations are critical factors affecting the geometric structure, the electronic band structure, van Hove singularities in density of states, the magnetic configurations, the dielectric functions, and energy loss functions. Furthermore, the meta-stable and stable exciton states are expected to survive in pristine and semi-hydrogenated group IV monolayers, respectively. The theoretical predictions established in this work are important not only for basic science but also for high-tech applications.